Water-Soluble Formulations of Curcumin and Eugenol Produced by Spray Drying - Iskra Z. Koleva; Katya Kamenova; Petar D. Petrov; Christo T. Tzachev (Pharmaceuticals, 2025)
Background/Objectives: In this study, we present a green, scalable platform for the production of water-dispersible powders co-encapsulating the lipophilic bioactives curcumin (Cur) and eugenol (Eug) within the amphiphilic polymer Soluplus® (SP) via low-temperature spray drying. Methods: The amount of Cur (1%, 5%, and 10%) and Eug (5%, 10%, 15%, and 20%) was varied to achieve single- and double-loaded water-soluble powders with the maximum amount of active substances. The powders containing a higher loading of Cur, 5% and 10% (and Eug), were obtained from water/ethanol mixtures (2:1 and 5:1 v/v ratio), while the formulation with 1% of Cur was spray-dried by using water as a solvent. Results: By leveraging aqueous or aqueous–ethanolic feed systems, we achieved high loading of the bioactive substances—up to 10% Cur and 20% Eug (w/w)—while minimizing organic solvent use. Myo-inositol was incorporated as a stabilizing excipient to modulate particle morphology, improve powder flowability, and enhance redispersibility. Physicochemical characterization revealed nanoscale micellization (53–127 nm), amorphization of both actives as confirmed by XRD and DSC, and the absence of crystalline residue. Encapsulation efficiencies exceeded 95% for Cur and 93% for Eug. Dissolution tests demonstrated a rapid release from the 5% Cur/5% Eug formulation (>85% in 5 min), while higher-loaded single-formulations showed progressively slower release (up to 45 min). Conclusions: This work demonstrates a robust and environmentally responsible encapsulation strategy, suitable for delivering poorly water-soluble phytochemicals with potential applications in oral nutraceuticals and pharmaceutical dosage forms.